Postwar architecture between Italy and the UK exchanges and transcultural influences. (UCL PRESS, 2021)
Postwar Architecture Between Italy and the UK explores the intellectual exchange between architects, urbanists and architectural historians in the two countries during the 1940s to 1970s, and its legacy.